2021
DOI: 10.3390/ma14102570
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Friction Phenomena of Ti-6Al-4V Sheets Based on Backward Elimination Regression and Multi-Layer Artificial Neural Networks

Abstract: This paper presents the application of multi-layer artificial neural networks (ANNs) and backward elimination regression for the prediction of values of the coefficient of friction (COF) of Ti-6Al-4V titanium alloy sheets. The results of the strip drawing test were used as data for the training networks. The strip drawing test was carried out under conditions of variable load and variable friction. Selected types of synthetic oils and environmentally friendly bio-degradable lubricants were used in the tests. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
0
13
0
1
Order By: Relevance
“…It is a two-phase alloy, characterized by a low density and very good corrosion resistance. It also shows good machinability and good mechanical properties, especially high mechanical strength in relation to its density [ 15 , 16 , 17 ]. However, recent research proves that the main elements contained in the Ti-6Al-4V alloy also have negative impacts on the human body.…”
Section: Introductionmentioning
confidence: 99%
“…It is a two-phase alloy, characterized by a low density and very good corrosion resistance. It also shows good machinability and good mechanical properties, especially high mechanical strength in relation to its density [ 15 , 16 , 17 ]. However, recent research proves that the main elements contained in the Ti-6Al-4V alloy also have negative impacts on the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, as can be seen from Figure 5, recovery of the scratch groove in the EBAM sample (41%) is even smaller than in the wrought sample (43%). According to the above proposed model, this can be attributed to the reverse α →α phase transformation resulting in volume shrinkage in the scratch groove, which could be induced by tensile stresses behind the moving indenter due to the high value of the coefficient of friction [40].…”
Section: Discussionmentioning
confidence: 99%
“…The unfavorable phenomena accompanying the SPIF and TPIF of titanium alloys can be limited by appropriate surface treatment of the tools and the use of appropriately selected technological lubricants [ 141 , 142 ]. Due to the fact that most of the lubricants used in sheet metal forming (SMF) processes belong to the group of synthetic oils, in recent years research has been conducted on replacing mineral oils with biodegradable vegetable oils [ 143 , 144 ], including those with the addition of nanopowders [ 145 , 146 , 147 ]. Trzepieciński et al [ 144 ] tested the tribological properties of Ti-6Al-4V titanium alloy sheets in a strip drawing test using five kinds of vegetable oils: palm oil, rapeseed oil, olive oil, sunflower oil and soybean oil.…”
Section: Surface Qualitymentioning
confidence: 99%
“…Due to the fact that most of the lubricants used in sheet metal forming (SMF) processes belong to the group of synthetic oils, in recent years research has been conducted on replacing mineral oils with biodegradable vegetable oils [ 143 , 144 ], including those with the addition of nanopowders [ 145 , 146 , 147 ]. Trzepieciński et al [ 144 ] tested the tribological properties of Ti-6Al-4V titanium alloy sheets in a strip drawing test using five kinds of vegetable oils: palm oil, rapeseed oil, olive oil, sunflower oil and soybean oil. It was found that increasing the load at a constant value of kinematic viscosity of lubricant reduces the value of the coefficient of friction (COF).…”
Section: Surface Qualitymentioning
confidence: 99%